Cost accounting and costing of healthcare services: theory and practice - Sysiuk, Svitlana; Kyryk, Vasyl (Herald of Economics, 2025)
Introduction. As a result of the healthcare reform, medical institutions in Ukraine were transformed into municipal enterprises, granting them financial autonomy and the ability to receive budgetary funds directly for the services provided through the system of a national purchaser, as well as to offer paid services. This financing approach necessitates the calculation of the cost of medical services and the proper accounting of related expenses. The restructuring of healthcare institutions has fostered competition for patients and raised the standards for service quality, which directly depends on the availability of financial, material-technical resources, and qualified personnel.The purpose of the article is to investigate the specifics and challenges of accounting and cost calculation of medical services in the context of healthcare reform.Research methods. Using critical analysis, graphic methods, and formalization, a sequence diagram for the costing process of paid medical services was developed and its key components described. A block diagram illustrating the algorithm for calculating the production cost of a medical service was constructed using formalization and generalization methods. The tabular method helped to demonstrate the application results of this algorithm and to determine the cost components for their reflection in accounting records. By applying scientific methodological tools, directions for solving management tasks related to the accounting and costing of medical services were proposed, taking into account the specific nature of the healthcare sector.Research results. Current approaches and sources of healthcare financing were analyzed, with particular attention given to issues of financial support. Sector-specific attributes and the cost structure of medical services were identified, along with an algorithm for cost formation under modern conditions. The necessity for modifying the costing process was justified, given the industry-specific characteristics not addressed by existing regulations. Based on this, the system of analytical accounting accounts was refined, and further problematic issues requiring scientific resolution were substantiated.Prospects. To improve the costing process, it is advisable to explore and enhance the methodology, using the block diagram developed in this study to identify tasks for potential software implementation.